Level of Creative Self-Efficacy among Deaf and Hearing Students at Al Ain University - Ellala, Ziyad kamel (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify the level of creative self-efficacy among deaf and hearing students at Al Ain University. The sample consists of (145) undergraduate male and female students as follows: (70) deaf students divided into (33) males and (37) females. The other (75) hearing students are (36) males and (39) females. Therefore, Abbott (2010) scale is adopted to measure the level of creative self-efficacy. The results show a high creative self-efficacy level, they also indicate statistically significant differences in favor of the hearing students on the total score of creative self-efficacy and on the dimension of self-efficacy in creative performance. Finally, the study concludes several recommendations discussed in the last section.